2022
DOI: 10.3390/s22134797
|View full text |Cite
|
Sign up to set email alerts
|

As-Doped h-BN Monolayer: A High Sensitivity and Short Recovery Time SF6 Decomposition Gas Sensor

Abstract: SF6 is a common insulating medium of gas-insulated switchgear (GIS). However, it is inevitable that SF6 will be decomposed due to partial discharge (PD) in GIS, which will cause hidden dangers to the safe and stable operation of equipment. Based on the DFT method, the two-dimensional nano-composite As-doped h-BN (As-BN) monolayer was proposed. By modeling and calculating, the ability of an As-BN monolayer as a specific sensor for SO2F2 (compared with an H2O adsorption system and CO2 adsorption system) was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recovery time (τ) 49 is an important factor to illustrate the rate of adsorbate's desorption from the substrate. Desorption and adsorption energies are equal since the adsorbate and substrate interact with each other, then recovery time can be determined as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Recovery time (τ) 49 is an important factor to illustrate the rate of adsorbate's desorption from the substrate. Desorption and adsorption energies are equal since the adsorbate and substrate interact with each other, then recovery time can be determined as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Long et al showed through theoretical research that the system with As replacing N atom in BN has strong adsorption specificity, high sensitivity, and short recovery time for SO 2 F 2 gas molecules. 121 By adding a P atom to the B position, the insulating properties of original BN are transformed into semiconducting properties. F and Cl both belong to the halogen group and are effective in subdividing the band gap when replacing the B atom.…”
Section: Doping Of Graphene (G)mentioning
confidence: 99%
“…It can be seen that the sensitivity of SiC 2 N toward O-containing VOCs and NH 3 is high (8.17× > 10 4 ) within the normal working temperature range (300-400 K). In addition, the sensitivity of some other sensor materials reported in previous studies is summarized in Table S1 [36,[54][55][56][57][58][59][60]. The sensitivity of SiC 2 N toward O-containing VOCs and NH 3 is comparable to or higher than some well-established gas sensors such as Si-GreenP toward acetone (~10 8 at room temperature) [36], vacancy-doped black phosphorus toward CO 2 (1254%, 298 K) [56], Rh-BN toward SO 2 (4.79 × 10 7 , 298 K) [54], and so on, showing superior sensor ability.…”
Section: Sensor Explanation Of Simentioning
confidence: 99%